Does Similarity Breed Connection? - An Investigation in Blogcatalog and Last.fm Communities - Bisgin, Halil; Agarwal, Nitin; Xiaowei Xu (2010 Second International Conference on Social Computing, 2010)
Similarity breeds connections, the principle of homophily, has been well studied in existing sociology literature. Several studies have observed this phenomenon by conducting surveys on human subjects. These studies have concluded that new ties are formed between similar individuals. This phenomenon has been used to explain several socio-psychological concepts such as segregation, community development, social mobility, etc. However, due to the nature of these studies and limitations because of involvement of human subjects, conclusions from these studies are not easily extensible in online social media. Social media, which is becoming the infinite space for interactions, has exceeded all the expectations in terms of growth and user participation, for reasons beyond human mind. New ties are formed in social media similarly as they would emerge in real-world. However, given the differences between real-world and online social media, do the same factors that govern the construction of new ties in real-world also govern the construction of new ties in social media? In this article, we study this extremely significant question. We propose a systematic approach by studying two online social media sites, BlogCatalog and Last.fm at varying granularity of interactions and report our findings along with some interesting observations.